Muscle‐derived exosomes encapsulate myomiRs and are involved in local skeletal muscle tissue communication. Issue 2 (23rd January 2021) - Mytidou, Chrystalla; Koutsoulidou, Andrie; Katsioloudi, Anna; Prokopi, Marianna; Kapnisis, Konstantinos; Michailidou, Kyriaki; Anayiotos, Andreas; Phylactou, Leonidas A.
Abstract: Exosomes are extracellular vesicles that are released from most cell types encapsulating specific molecular cargo. Exosomes serve as mediators of cell‐to‐cell and tissue‐to‐tissue communications under normal and pathological conditions. It has been shown that exosomes carrying muscle‐specific miRNAs, myomiRs, are secreted from skeletal muscle cells in vitro and are elevated in the blood of muscle disease patients. The aim of this study was to investigate the secretion of exosomes encapsulating the four myomiRs from skeletal muscle tissues and to assess their role in inter‐tissue communication between neighboring skeletal muscles in vivo. We demonstrate, for the first time, that isolated, intact skeletal muscle tissues secrete exosomes encapsulating the four myomiRs, miR‐1, miR‐133a, miR‐133b, and miR‐206. Notably, we show that the sorting of the four myomiRs within exosomes varies between skeletal muscles of different muscle fiber‐type composition. miR‐133a and miR‐133b downregulation in TA muscles caused a reduction of their levels in neighboring skeletal muscles and in serum exosomes. In conclusion, our results reveal that skeletal muscle‐derived exosomes encapsulate the four myomiRs, some of which enter the blood, while a portion is used for the local communication between proximal muscle tissues. These findings provide important evidence regarding novel pathways implicated in skeletal muscle function.